WANITA KARIR DALAM PANDANGAN HADIS - Khoirul Anwar Umar Harahap (Institut Agama Islam Negeri Padangsidimpuan, 2020)
This journal was created to find out that career women in the view of Islam are allowed or strictly prohibited in Islam. Therefore, it is necessary to study whether women are allowed to work in Islam, as well as women with careers who meet the requirements and do not violate Islamic law. The problem of this discussion is taken qualitatively from a literature study by researchers. The main problem in this research is career women in hadith. The subject matter is described in detail into several sub-problems or questions, namely: Definition of career women, legal basis, characteristics of women, requirements for career women, because of career women, positive and negative impact of career women.